"We are Still Running around with the Same Rules, but We are Not the Same We Were 20 Years Ago" – Exploring the Perceptions of Youth Justice Professionals on Secure Training Centres. Issue 4 (2nd October 2022) - Paterson-Young, Claire
ABSTRACT: Debates on the incarceration of children in residential settings has been ongoing for decades, with the United Nations Convention of the Rights of the Child and academic literature acknowledging that custody is not in the best interest of the child. In England, the problems associated with placing children in custody have been documents since 1999 and, nearly twenty years later, a BBC Panorama exposed the abuse of children at the hands of staff in the same Secure Training Center. This paper examines staff' and other professional perceptions as to the purpose and direction of Secure Training Centers, youth custodial environments, through thematic analysis of semi-structured interviews with staff members employed in Secure Training Centers and other professionals in the youth justice sector (i.e. Social Workers, Youth Offending Officers and Managers). It seeks to identify perceptions on the purpose and challenge of Secure Training Centers in supporting children who have experiences adverse circumstances resulting in trauma. It illustrates the need for embedding trauma-informed "Child First" approaches in Secure Training Centers, and youth custodial environments globally, to enable staff to adequately support children to build empowering relationships.